The Grey Zone of Stakeholder Engagement : Misalignment as a Manifestation of Greyness in Stakeholder Collaboration - Blomberg, Annika; Hannula, Anna; Kujala, Johanna (Wiley, 2026)
This study identifies and conceptualises the grey zone of stakeholder engagement and explores how it manifests in a collaborative context related to the promotion of a circular economy. While prior research on stakeholder engagement has highlighted the positive, value-creating bright side or the harmful dark side of stakeholder engagement, we show that even when stakeholders have a shared goal and engagement is organised collaboratively, it contains a more subtle space where everyday challenges and inconveniences unfold. Drawing on a qualitative analysis of interviews with 43 circular-economy stakeholders, we identify and conceptualise this grey zone and demonstrate how it manifests in misalignment of practices and mindsets at the individual, organisational, and societal levels. Recognising the grey zone as a natural and unavoidable part of stakeholder engagement is essential for understanding stakeholder collaboration and strengthening stakeholder theory and its applicability.